2018
DOI: 10.1056/nejmoa1708984
|View full text |Cite|
|
Sign up to set email alerts
|

Brentuximab Vedotin with Chemotherapy for Stage III or IV Hodgkin’s Lymphoma

Abstract: BACKGROUND Brentuximab vedotin is an anti-CD30 antibody–drug conjugate that has been approved for relapsed and refractory Hodgkin’s lymphoma. METHODS We conducted an open-label, multicenter, randomized phase 3 trial involving patients with previously untreated stage III or IV classic Hodgkin’s lymphoma, in which 664 were assigned to receive brentuximab vedotin, doxorubicin, vinblastine, and dacarbazine (A+AVD) and 670 were assigned to receive doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
436
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 603 publications
(505 citation statements)
references
References 25 publications
7
436
1
11
Order By: Relevance
“…More recently, brentuximab vedotin (BV), an anti‐CD30 antibody‐drug conjugate that is highly active in the relapsed/refractory setting, was also tested in advanced stage patients. The ECHELON study compared ABVD to BV plus AVD (BV+AVD) in patients with advanced stage disease (Connors et al , ) (Table ). The trial demonstrated modest improvement in modified PFS, with an absolute difference of 4·9 percentage points (HR for an event of progression, death, or modified progression, 0·77, CI; 0·6–0·98, P = 0·04) with BV+AVD as compared with ABVD without difference in OS with short follow‐up.…”
Section: Adult Therapeutic Approachesmentioning
confidence: 99%
“…More recently, brentuximab vedotin (BV), an anti‐CD30 antibody‐drug conjugate that is highly active in the relapsed/refractory setting, was also tested in advanced stage patients. The ECHELON study compared ABVD to BV plus AVD (BV+AVD) in patients with advanced stage disease (Connors et al , ) (Table ). The trial demonstrated modest improvement in modified PFS, with an absolute difference of 4·9 percentage points (HR for an event of progression, death, or modified progression, 0·77, CI; 0·6–0·98, P = 0·04) with BV+AVD as compared with ABVD without difference in OS with short follow‐up.…”
Section: Adult Therapeutic Approachesmentioning
confidence: 99%
“…Similarly, recent results of the ECHOLON‐1 study of BV combined with AVD showed the well‐known effect of treatment intensification in older HL patients (Connors et al , ). The intensified A+AVD regimen had increased severe toxicity in older patients including febrile neutropenia in more than one third of the patients (37%) (Connors et al , ). In accordance with previous results using ABVD, this suggests that AVD might not be the ideal chemotherapy‐backbone for simultaneous combination to novel substances in older HL patients (Böll et al , ; Evens et al , ).…”
Section: Discussionmentioning
confidence: 71%
“…This was an unblinded study and therefore potentially prone to bias in this respect. With a median follow‐up of 2 years there was a 4·9% difference in modified PFS in favour of the AVD‐BV group with no difference in 2‐year EFS or OS (Connors et al , ). A higher incidence of grade 3–4 peripheral neuropathy and febrile neutropenia was reported in the BV+AVD group but the myelosuppression could be mitigated by the use of prophylactic granulocyte colony‐stimulating factor.…”
Section: Initial Therapy In Younger Patientsmentioning
confidence: 99%